Mathematical Model for the Bulk Polymerization of Styrene Chemically Initiated by Sequential and Total Decomposition of the Symmetrical Cyclic Trifunctional Initiator Diethyl Ketone Triperoxide - Berkenwald, Emilio (2015)
This work experimentally and theoretically investigates the use of the symmetrical cyclic trifunctional initiator diethyl ketone triperoxide (DEKTP) in the bulk polymerization of styrene (St). The study focused on temperatures of 150 to 200°C, considering chemical initiation by both sequential and total decomposition reactions. The experimental work consisted of a series of isothermal batch polymerizations at higher temperatures, 150 and 200°C, with an initiator concentration of 0.01 mol/L. The mathematical model is based on a kinetic mechanism that includes thermal and chemical initiation (both sequential and total decomposition reactions), propagation, transfer to monomer, termination by combination and re-initiation reactions. Experimental and theoretical results show that the decomposition mechanism of the initiator is modified by the reaction temperature and can be modeled as a set of two parallel reactions with different temperature dependences. The developed mathematical model simulates the bulk polymerization of St in the presence of DEKTP for a wide temperature range (120–200°C). It was found that due to these two decomposition mechanisms, the system may behave as a “dead-end” polymerization system above a certain temperature, yielding low molecular weights and a limiting conversion value. Simulation results indicate the value of this temperature to be about 185°C.